Original paperEarly outcome of aortic valve replacement with mechanical prosthesis in patients with aortic stenosis. Is patient-prosthesis mismatch a significant clinical problem? - Jander, Sławomir; Bitner, Mirosław; Jegier, Bogdan; Ostrowski, Stanisław; Jaszewski, Ryszard (Archives of Medical Science, 2007)
Introduction: Prevalence of aortic valve disease increases with a population’s aging. Aortic valve replacement (AVR) is one of the most frequently performed procedures in cardiac surgery centres. Patient-prosthesis mismatch (PPM) is believed by some authors to be a significant clinical problem. The aim of the present study was to assess early results of AVR in patients with isolated aortic valve stenosis, with special regard to haemodynamic parameters and PPM. Material and methods: Forty-eight consecutive patients (28 men and 20 women) aged mean 59.3±12.1 years, who underwent AVR with a mechanical prosthesis, in the Department of Cardiac Surgery, Medical University of Lodz, Poland in 2003, were retrospectively analyzed. Results: The in-hospital postoperative mortality in the study group was 4.2%. The most common postoperative complications were arrhythmia and low cardiac output syndrome (LCOS), which occurred in 5 patients (10.4%) each. At discharge from hospital no patient met the criterion of PPM (effective orifice area index – EOAI of 0.85 cm 2 /m 2 or lower). Significant improvement was observed in mean New York Heart Association (NYHA) class and mean maximal valvular gradient (respectively 2.3±0.5 vs. 1.4±0.7 and 87.1±19.1mmHg vs. 26.4±6.5 mmHg, p<0.05 for both values). Conclusions: In the analyzed group the early results of AVR with mechanical prosthesis are good and no case of PPM was observed.